P209 A pilot quality improvement (QI) initiative to improve the discharge planning process for patients with complex care needs at temple street children's hospital (TSCUH), dublin. (June 2019) - Vaish, Shashi; Power, Gráinne; Fagan, Claire; Fitzgerald, Elaine; Ryan, Sharon
Abstract : Background: Improvements in medical care have resulted in increasing numbers of children with complex care needs. These patients have substantial care needs resulting in functional limitations that may require tailored technological assistance (Cohen et al. 2011). These increased medical needs can result in prolonged hospital stay with a significant impact on the lives of the patient and their family. Discharge planning is an important aspect of patient care and can be challenging to organize for these patients. Currently there is a lot of disparity in the co-ordination of discharge or transfer process for these patients throughout our hospital. The has had a negative impact, some of which include, a delay in recognizing these patients and their needs, poor communication between health care professions, duplication of work and poor patient experience. Aims: A pilot QI initiative to improve the discharge planning process for long stay children with complex care needs by decreasing the time to initiate the discharge planning from more than 100 days to less than 60 days of in-patient stay on a ward at Temple Street Children's University Hospital, Dublin. Methods: Baseline data was collected and analysed to establish the median number of days before discharge planning was initiated for five children with complex care needs who were long-stay in-patients (i.e. for more than 30 days) on a particular ward at TSCUH. A patient-centred approach to improving inpatient discharge planning process for long-stay patients with complex care needs was created. A number of plan, do, study and act (PDSA) cycles were conducted in developing a baseline data collection method and a criteria based referral pathway to allow for initiation of a standardised discharge process for these patients. Early recognition of these patients assessed the impact on initiating the discharge planning process for patients admitted to one of the wards at TSCUH. Results/Findings: Data collection and collation is on-going and should be complete by March 2019.